Lower feed and water consumptions and body weight in rats consuming aqueous extracts or ground leptadenia pyrotechnica: DOI: 10.48129/kjs.14617 - Alsahafi, Bushra; Mahassni, Sawsan (Kuwait Journal of Science, 2023)
Leptadenia pyrotechnica (LP) is used in folk medicine for the treatment of different ailments. No published studies on the affects of ground and aqueous LP extract in laboratory animals exist. Thus, this study is the first to investigate the difference between using ground or aqueous extract of LP on body weight parameters and consumptions of feed and water in young adult albino rats. Four groups (one rat of either sex for each group) were administered 25%, 50% and 75% ground LP mixed with the regular feed for 7 days, while the control rats were given the regular diet. Five groups (two rats of either sex for each group) were orally gavaged with 3, 9, 15 and 20 g LP extract/kg body weight, while the control group was gavaged with water, daily for 14 days. Findings were compared with the control groups. The mean body weight loss and feed inefficiency ratios for the ground LP groups were higher, leading to lower feed and water intakes. Rats that consumed 15 and 20 g LP extract/kg had higher mean body weight loss and feed inefficiency ratios, and lower water and feed intakes for the first but not for the second week. Therefore, both forms of LP affect weights and consumptions of water and feed during the first week. Thus, while using LP for any medicinal or therapeutic uses in humans, any affects on weight or feed and water consumptions may last only for a week.